The Accuracy of General Government Balance Forecasts in Romania - Mihaela Simionescu (CES Working Papers, 2015)
Economic forecasts are an essential building block for a budgetary anticipation in order to determine the budgetary objectives and to sustain the tax and expenditure plans. In Romania the surveillance process is ensured by the use of budget programs. The aim of this paper is to improve the budgetary planning by recommending the use of the forecasted general budget balance provided by the institution with the highest accuracy during the crisis (2008-2013). More types of projections were analyzed during the recent economic crisis and the IMF forecasts for this indicator outperformed those provided by Dobrescu model and the European Union. Therefore, the recommendation is related to the use of IMF predictions in establishing the next budgetary plan for 2014 and 2015. Moreover, this research also brings improvements in the methodological framework, by proposing some aggregated accuracy indicators (S1, S2, S3 and S measures) for solving the problem of contradictory results of different accuracy indicators.
Keywords: C51; C53; 330; general government balance; budget deficit; forecasts; accuracy